Th22 Cells Promote Osteoclast Differentiation via Production of IL-22 in Rheumatoid Arthritis - Miyazaki, Yusuke; Nakayamada, Shingo; Kubo, Satoshi; Nakano, Kazuhisa; Iwata, Shigeru; Miyagawa, Ippei; Ma, Xiaoxue; Trimova, Gulzhan; Sakata, Kei; Tanaka, Yoshiya (Frontiers in Immunology, 2018)
T helper (Th) cells can differentiate into functionally distinct subsets and play a pivotal role in inflammatory and autoimmune diseases such as rheumatoid arthritis (RA). Th22 cells have been identified as a new subset secreting interleukin (IL)-22. Although elevated levels of IL-22 in the synovial fluids of RA patients were reported, its pathological roles remain unclear. Here, we demonstrated that IL-22 was characteristically produced from CD3+CD4+CC-chemokine receptor (CCR)4+CCR6+CCR10+ cells and their ability of the production of IL-22 markedly exceeded that of other Th subsets and the subset, thereby, designated Th22 cells. Th22 cells were efficiently induced by the stimulation with tumor necrosis factor-α, IL-6, and IL-1β. Th22 cells were markedly infiltrated in synovial tissue in patients with active RA, but not in patients with osteoarthritis (OA). CCL17, CCL20 and CCL28, which are chemokine ligands of CCR4, CCR6 and CCR10, respectively, were abundantly expressed in RA synovial tissue compared to OA. By in vitro Trans-well migration assay, Th22 cells efficiently migrated towards CCL28. Co-culture of Th22 cells, which were sorted from peripheral blood, with monocytes in the presence of macrophage colony-stimulating factor and receptor activator of nuclear factor (NF)-κB ligand induced osteoclasts formation more efficiently than that of either Th1 cells or Th17 cells. Furthermore, IL-22 markedly augmented osteoclast differentiation by promoting nuclear factor of activated T cells c1 expression in CD14+ monocytes. Contrarily, the addition of IFN-γ to the culture significantly decreased osteoclasts number, whereas IL-17 had marginal effects. IL-22 neutralizing antibody inhibited osteoclast formation in the co-culture of Th22 cells with CD14+ monocytes. Collectively, the results indicated that Th22 cells, which co-express chemokine receptors CCR4, CCR6 and CCR10, possess strong potency of tissue migration and accumulate into inflamed synovial tissues where the ligands such as CCL28 are highly expressed. Thus, Th22 cells have the capacity to promote osteoclast differentiation through production of IL-22 and thus play a pivotal role in bone destruction in patients with RA.